Network models of posttraumatic stress symptoms across trauma types. (August 2018) - Benfer, Natasha; Bardeen, Joseph R.; Cero, Ian; Kramer, Lindsay B.; Whiteman, Sarah E.; Rogers, Travis A.; Silverstein, Madison W.; Weathers, Frank W.
Highlights: Network analysis was used to examine posttraumatic stress (PTS) symptoms as a function of trauma type. Three trauma types examined: motor vehicle accident, sexual assault, and sudden death. Sexual assault network was most consistent with DSM-5 conceptualization of PTSD. Sudden death was least consistent with DSM-5 PTSD. Centrality in the pooled network was highest for anhedonia and dysphoria and lowest for amnesia. Abstract: Evidence suggests that posttraumatic stress (PTS) disorder (PTSD) symptom presentations may vary as a function of index trauma type. Network analysis was employed in the present study to examine differences in PTS symptom centrality (i.e., the relative influence of a symptom on the network), and PTS symptom associations across three trauma types: motor vehicle accident (MVA), sexual assault (SA), and sudden accidental/violent death of a loved one (SAD). The final sample comprised 554 female undergraduates who had experienced a MVA ( n = 226), SA ( n = 222), or SAD ( n = 106) per Diagnostic Statistical Manual—Fifth Edition ( DSM-5 ) criteria. Within the pooled network, anhedonia and dysphoria emerged as the most central symptoms, while trauma-related amnesia was the least central. The SA network was largely consistent with the DSM-5 conceptualization of PTSD. In contrast, the SAD network was the least consistent with the DSM-5 conceptualization of PTSD, and centrality estimates for the SAD network were inconsistent with the MVA and SA networks. Findings of the current study suggest a need to consider index trauma type as an important factor in the ontology of PTSD. Findings also add to the ongoing discussions about the suitability of SAD as a PTSD-relevant trauma type and about the importance of trauma-related amnesia as a PTSD symptom.